The Effectiveness of MRP System to Forecast the Accuracy Inventory Requirement - Rizad Md Sapry, Hairul; L’ wiey Anak Tawi, Lorio; Rahman Ahmad, Abd; Baskaran, Shathees (International Journal of Engineering and Technology, 2018)
The implementation of MRP systems play a crucial role in today's manufacturing process in providing valuable information not only to both marketing and manufacturing team, but the organization as a whole. Yet, MRP system does not possess the capability of doing everything. There are few limitations within MRP system in relation to flexibility and adaptability to the changes of the external environment. The objective of the study is to investigate the capability of MRP system in providing an accurate forecast for the inventory requirement. The study was conducted through a qualitative case study approach by analyzing historical data of a single multinational organization which is currently implementing MRP system in managing their inventory. Few supply chain performance indicators were applied to measure the effectiveness of MRP system in managing the inventory process. The result revealed that MRP system under investigation is the central engine for managing inventory and ensuring customer service. However, MRP system require valid and reliable data optimized by a set of pre-defined parameters to run effectively with possible interface with other supporting software.Â This study suggests other supporting software such as Stock Model to be interfaced with the MRP system for greater flexibility and adaptability in respond to foreseeable or unforeseeable external changes.Â